2023
DOI: 10.3389/fmicb.2023.1212996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of drought stress-mitigating Rhizobium from faba bean (Vicia faba L.) in the Chinese Qinghai-Tibet Plateau

Ping Li,
Changcai Teng,
Jinfa Zhang
et al.

Abstract: Rhizobium-driven symbiotic nitrogen-fixation in legumes not only benefits the growth but also enhances the stress tolerance of plants. Isolating and characterizing efficient, drought-tolerant rhizobia is a central goal for improving crop yields in arid regions. Here, we phylogenetically and biochemically characterized a novel strain of Rhizobium (‘QHCD11’) sampled from the root nodules of faba beans growing in an arid agricultural area in Qinghai-Tibet. We further tested the drought tolerance of the strain as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Stress-resistant rhizobia have significant potential in agricultural production. Li et al isolated the drought-resistant rhizobacterium 'QHCD11' from the root nodules of faba beans growing in an arid agricultural area in the Qinghai-Tibet Plateau, and they found that the inoculation of faba beans with QHCD11 was an environmentally friendly strategy for mitigating drought stress in arid and semi-arid crops [36]. Rhizobium STDF-Egypt19 isolated from the root nodules of faba beans grown in sludge-contaminated fields in Upper Egypt were used as an inexpensive and efficient bioremediation technology for the removal and recovery of heavy-metal ions from aqueous solutions [37].…”
Section: Application Analysis Of Rhizobia From Different Areasmentioning
confidence: 99%
“…Stress-resistant rhizobia have significant potential in agricultural production. Li et al isolated the drought-resistant rhizobacterium 'QHCD11' from the root nodules of faba beans growing in an arid agricultural area in the Qinghai-Tibet Plateau, and they found that the inoculation of faba beans with QHCD11 was an environmentally friendly strategy for mitigating drought stress in arid and semi-arid crops [36]. Rhizobium STDF-Egypt19 isolated from the root nodules of faba beans grown in sludge-contaminated fields in Upper Egypt were used as an inexpensive and efficient bioremediation technology for the removal and recovery of heavy-metal ions from aqueous solutions [37].…”
Section: Application Analysis Of Rhizobia From Different Areasmentioning
confidence: 99%